Hot rods (Blazers horsepower, ,, 2007)
Describes hot rods, their main features, and how they are built.
Making a hot rod , Custom cars , Engine power , Showing off , Hot rod parts , Glossary , Read more , Internet sites , Index.

Hot hot rods (Fast rides, ,, 2011)
Describes a variety of hot rods, including Ford vehicles, Volkswagen Beetles, trucks, motorcycles, and others.
Hot hot rods , Hot mods , Fabulous Fords , Breathtaking bugs , Terrefic trucks , Mad motorcycles , Hollywood mobiles , Crazy cars , Super rods.

Hot rods (Epic. Full throttle, ,, 2019)
"Engaging images accompany information about hot rods. The combination of high-interest subject matter and light text is intended for students in grades 2 through 7"--
4x4 trucks , ATVs , Dirt bikes , Hot rods , Lowriders , Monster trucks , Motocross cycles , Stock cars.

Wild about hot rods (Wild rides, ,, 2008)
Introduces hot rods and discusses what they look like, their history, customizing a hot rod, cars strictly for show or for racing, and related topics.

George Barris: cruisin' back to the 50's (Westlake Entertainment Group, 2004)
"Cruise with us down to Culver City, CA to the George Barris 'Back to the 50's' car show, presented by 'The King of the Kustomizers' Mr. George Barris and produced by Debbie Baker. The show is set in the gorgeous atmosphere of southern California sunshine along with family and friends, 50's music, red lipstick and bobby socks. View up close high quality, original customs, muscle cars, hot rods as well as several TV and movie cars from George's personal collection. This fun and entertaining show has something for the whole family, and puts you right in the center of the action!"

The fate of the furious (Universal Pictures Home Entertainment, 2017)
When a mysterious woman seduces Dom into the world of terrorism and a betrayal of those closest to him, the crew face trials that will test them as never before.

Fast X (Universal, 2023)
Over many missions and against impossible odds, Dom Toretto and his family have outsmarted, out-nerved and outdriven every foe in their path. Now, they confront the most lethal opponent they've ever faced: a terrifying threat emerging from the shadows of the past who's fueled by blood revenge, and who is so determined to shatter this family that they'll need to collaborate with old enemies to defeat him.

Furious 7 (Universal, Universal Studios, 2015)
Deckard Shaw is out for revenge against Dominic Toretto and his crew, following the death of his brother in ₁Fast & Furious 6.₂ Before Shaw can do that, Dom plans to take him out first with help from Brian, Ronan, Tej, and Letty.

The fast and the furious: Tokyo drift (Universal Studios Home Entertainment, Universal Pictures, 2013)
To avoid jail time, street racer Sean Boswell is sent to live with his father, who is in the military and serving in Tokyo. There he discovers drift racing. After losing a race to Yakuza-connected D.K., the Drift King, Sean has to enter the Tokyo underworld to find a way to pay his debt.

Fast five (Universal Studios Home Entertainment, 2011)
After Brian and Mia break Dom out of jail, they find themselves trapped in Rio de Janeiro and on the run from the law. Now one last job stands between them and freedom, but will they make it before the corrupt businessmen, or the feds, catch up to them?
Extended version , Theatrical version.

2 fast 2 furious (Universal Studios Home Entertainment, 2009)
Ex-cop Brian O'Conner has left Los Angeles due to his illegal actions and soars the streets of Miami making money here and there by street racing. Watched by Customs Agent Monica Fuentes, Brian is caught by the police and is given a deal by Agents Markham and Bilkins. They want Brian to go undercover and try to bring down drug lord Carter Verone. In exchange, his criminal record will be erased. Brian agrees but only if he is given permission to choose his partner. He heads home to California where he recruits his old friend Roman Pearce to help him. Roman agrees, but only for the same deal Brian was offered. With Monica's help, Brian and Roman work together to take down Verone.

Fast & furious (Universal Studios Home Entertainment, 2009)
Dom Toretto is a former street racer who, along with his crew, hijacks an oil truck out on the highway. Dom is living the life of a fugitive in the Dominican Republic, but after suffering a devastating personal loss, he is driven by revenge to return to Los Angeles to bring down an elusive drug smuggler. He is reunited with undercover FBI agent Brian O'Connor who let him go eight years earlier. Brian is also on the case of the drug smuggler and he must come to terms with Dom and make amends with Dom's sister, whom he betrayed in his original pursuit of Dom.